ANALISIS KELAYAKAN USAHA BROILER DI KELURAHAN TARATARA I KECAMATAN TOMOHON BARAT KOTA TOMOHON - Santa, N M; Kalangi, L S; Wantasen, E (ZOOTEC, 2020)
FEASIBILITY ANALYSIS OF BROILERS IN TARATARA I VILAGE WEST TOMOHON DISTRICT TOMOHON CITY. Broiler business which is run by partnership pattern, is one of the suppliers of food products that source animal protein. Increased demand for broiler meat, needs to be followed by business development that has previously calculated the level of business feasibility. This study aims to determine the feasibility of a broiler business based on Net Present Value (NPV), Internal Rate of Return (IRR), R/C, Net B/C. The study was conducted by taking a case in a broiler business with a capacity of 3.000 animals, with 6 maintenance periods per year, which has been undertaken since 2015, located in Taratara I Village, Tomohon Barat District. The results showed that the average cost wasIDR. 91.784.947/period while income was IDR. 99.873.539/period, and profit wasIDR 8.088.592/period. The NPV value was IDR 26.837.471 which had a positive number, an IRR value was 19,03%, andÂ  both of R/C Â and Net B/C was higher than 1, so that the broiler business can be implemented and developed.